2015
DOI: 10.1016/j.juro.2015.01.071
|View full text |Cite
|
Sign up to set email alerts
|

Early Drastic Decrease in White Blood Count Can Predict Uroseptic Shock Induced by Upper Urinary Tract Endoscopic Lithotripsy: A Translational Study

Abstract: The white blood count decreased drastically within the first 2 hours during the development of uroseptic shock. This could be an ideal predictor of uroseptic shock after upper urinary tract endoscopic lithotripsy. In patients with high risk factors for uroseptic shock the white blood count should be measured within 2 hours after upper urinary tract endoscopic lithotripsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 21 publications
(17 reference statements)
5
20
0
Order By: Relevance
“…In terms of surgery, a number of studies have reviewed the risk factors for the occurrence of postoperative sepsis and mortality following endourological treatment: Presence of kidney stones; large stone burden; female sex; diabetes mellitus; renal insufficiency; high pressure in the collecting system; and long surgery times were identified to be risk factors for sepsis following operation (9)(10)(11)30). Wu et al (12) demonstrated an association between the early marked decrease in WBC count and uroseptic shock induced by upper urinary tract endoscopic lithotripsy. However, there was no unified, widely accepted and standardized criteria for predicting the prognosis of these patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of surgery, a number of studies have reviewed the risk factors for the occurrence of postoperative sepsis and mortality following endourological treatment: Presence of kidney stones; large stone burden; female sex; diabetes mellitus; renal insufficiency; high pressure in the collecting system; and long surgery times were identified to be risk factors for sepsis following operation (9)(10)(11)30). Wu et al (12) demonstrated an association between the early marked decrease in WBC count and uroseptic shock induced by upper urinary tract endoscopic lithotripsy. However, there was no unified, widely accepted and standardized criteria for predicting the prognosis of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical procedure. The methods used to perform PCNL, URL and emergency ureteroscopic double J stenting procedures were analogous with other previously described methods (11,12,23). Patients with obstructive urolithiasis and suspected urosepsis, as diagnosed by the emergency physicians, were transferred to the urology department.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al (page 2116) from the People's Republic of China identified a practical predictor of UUTEL induced uroseptic shock in a rabbit model and validated results by retrospectively reviewing multicenter clinical records. 3 They ligated rabbit ureters and injected Escherichia coli solution in the renal pelvis to create the uroseptic shock model. White blood count (WBC) and other parameters were measured at different bacterial concentrations and intervals.…”
Section: Decreased White Blood Count Predicts Uroseptic Shock After Lmentioning
confidence: 99%
“…During PCNL for staghorn calculi, blood loss is significantly increased compared with that occurring in this procedure for other types of stone (6). Urosepsis after upper urinary tract endoscopic surgery is a life-threatening complication and considered to be associated with high intrapelvic pressure and large stone size (7). In addition, it remains controversial which procedures are best for patients with staghorn renal stone and concurrent urinary tract infection (UTI).…”
Section: Introductionmentioning
confidence: 99%